Helping people overcome suicidal thoughts, urges and behaviour : suicide-focused intervention skills for health and social care professionals - Bell, Lorraine, 1956- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Helping People Overcome Suicidal Thoughts, Urges and Behaviour draws together practical and effective approaches to help individuals at risk of suicide. The book provides a framework and outlines skills for anyone working with adults who present with suicidal thoughts or intent. Part 1 introduces a basic understanding of our knowledge about suicide and UK policy; Part 2 outlines the research into the treatment of suicidality and the general principles for working in the safest possible way. Part 3 outlines ten key psychological skills in the context of evidence-based best practice. The book also discusses the role of health and social care professionals in the prevention of suicide in the context of Covid-19. The book will be a valuable addition to the resources of professionals including psychotherapists, nurses, social workers, occupational therapists, prison and probation officers, drug and alcohol workers, general practitioners and support staff in any health or social care context"--
Includes bibliographical references and index.
Keywords: Suicide -- Great Britain -- Psychological aspects; Suicidal behavior -- Great Britain -- Prevention; Suicidal behavior -- Treatment -- Great Britain; Suicide -- Grande-Bretagne -- Aspect psychologique; Comportement suicidaire -- Traitement -- Grande-Bretagne.; Suicidal behavior -- Prevention; Suicidal behavior -- Treatment; Suicide -- Psychological aspects; Great Britain